1998
DOI: 10.1007/s004649900616
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic score to predict the difficulty of a laparoscopic cholecystectomy from preoperative variables

Abstract: Our model should help to select patients for either laparoscopic or open cholecystectomy based on the expected difficulties and the experience of the surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 8 publications
4
51
0
Order By: Relevance
“…Other studies have shown, however, that prior upper abdominal surgery is a significant risk factor for open conversion and either intraoperative or postoperative complications [6,14]. Our findings are in agreement with those of Schirmer et al [13], who reported higher complication and conversion rates as well as a longer hospital stay for patients with previous upper abdominal surgery than for those without previous upper abdominal surgery, although the operative times were similar in both groups.…”
Section: Discussionsupporting
confidence: 95%
“…Other studies have shown, however, that prior upper abdominal surgery is a significant risk factor for open conversion and either intraoperative or postoperative complications [6,14]. Our findings are in agreement with those of Schirmer et al [13], who reported higher complication and conversion rates as well as a longer hospital stay for patients with previous upper abdominal surgery than for those without previous upper abdominal surgery, although the operative times were similar in both groups.…”
Section: Discussionsupporting
confidence: 95%
“…Additionally, surgeons having more than 10 years' experience and surgeons having performed fewer than 500 LC converted more frequently. This could mean that, with experience, surgeons identified risks more rapidly during LC, while surgeons less skilled in laparoscopic techniques recognized that the laparoscopic approach might be technically too demanding in difficult cases of AC and preferred conversion to a primary open approach [3,[11][12][13][14]. Local disease-related factors, such as gangrenous cholecystitis or coexistent CBDS, were major predictive factors of conversion, in agreement with previous reports [13,14].…”
Section: Discussionsupporting
confidence: 83%
“…Evidence for factors that might contribute to surgical difficulty during LC are ambiguous despite several existing studies (preoperative radiological findings [4][5][6], the optimal timing for LC [3,7], indications of preoperative interventions such as percutaneous transhepatic gallbladder drainage [8,9], etc). Most of the previous publications have adopted either the duration of surgery [4][5][6] or open conversion rate [10][11][12][13][14] as surrogate markers for surgical difficulty. However, these factors are strongly affected by the skill of each surgeon and center's policy.…”
Section: Introductionmentioning
confidence: 99%